A Comparison of the Effectiveness of Emotionally Focused Therapy and Acceptance and Commitment Therapy in Improving Emotional Self-Regulation and Psychological Well-Being in Couples - Azandaryani, Mehri; Khajoei-Nejad, Gholamreza; Akbari Amarghan, Hossein (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study aimed to determine the effectiveness of emotionally focused therapy (EFT) in comparison with acceptance and commitment therapy (ACT) in improving emotional self-regulation, psychological well-being, and resilience of couples. Methods: The research was quasi-experimental and applied with a pretest-posttest design, a control group, and quarterly follow-up. The statistical population consisted of all couples with marital non-adjustment living in District 4 of Qom who visited counseling and psychotherapy centers in the second half of 2020. The convenience sampling method was performed. After the random assignment of experimental and control groups, the first experimental group received the emotionally focused therapy by Johnson (2012), and the second experimental group received the Acceptance and Commitment Therapy by Hayes and Strosahl (2010) in eight one-hour sessions. The data collection tool included difficulties in emotion regulation scale (DERS) by Gratz and Roemer (2004), and Ryff’s scale of the psychological well-being-short form (RSPWB) at three stages, pre-test, post-test, and follow-up. Data were analyzed using repeated-measures analysis of variance. Results: The results indicated the effects of emotionally focused therapy and acceptance and commitment therapy on emotional self-regulation (F=10.90, P=0.009) and psychological well-being (F=31.10, P=0.001), and stability of the effect at the follow-up stage. The results of Tukey’s post hoc test indicated that the difference between the two methods of couple therapy was not significant (P=0.31). Conclusion: The results suggest evidence that emotionally focused couple therapy and acceptance and commitment therapy were appropriate for improving and increasing emotional self-regulation and psychological well-being.